Modelling of P-wave velocity changes in coal seams with increased depth: a case study - Maciej Łapczyński; Zenon Pilecki; Krzysztof Krawiec; Artur Słomian; Elżbieta Pilecka; Tomasz Łątka (Scientific Reports)
Abstract Seismic profiling in a coal seam enables the determination of anomalous changes in the P-wave velocity compared to reference velocity at a specific mining depth, indicating potential stress changes. This information can improve the coal exploitation processes in advance at greater depths, especially in seismic hazard areas. This study aims to update the empirical mathematical formula for calculating reference P-wave velocities in coal seams by including new data measured at greater depths. The research was performed at the Zofiówka Coal Mine in the geological and mining conditions of the Upper Silesian Coal Basin in Poland. The analysis involved the study of 276 velocity values including 24 new velocity values measured at depths ranging from 704 to 1073 metres in the period 2009–2024. Through regression analysis, the standard model was modified. The new model provides more reliable velocity anomaly calculations and accurately reflects the geomechanical conditions at greater depths in the Zofiówka Coal Mine. The calculation procedure can be utilised to develop velocity models for various geological and geomechanical conditions in underground mines that exploit coal seams at continuously increasing depths.